Design of the Jokka Jokka Kemujan Tour E-Booklet as a Promotional Medium for Marine Ecotourism in Karimunjawa - Teresa Shevi Yuratama; Lintang Permata Sari Yuliadi; R. Mochamad Candra Wirawan Arief; Donny Juliandri Prihadi; Fanny Kristiadhi (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to design an effective promotional medium in the form of an e-booklet to share information about the Jokka Jokka Kemujan Tour as a marine ecotourism destination in Karimunjawa. It also seeks to examine how effective the e-booklet is in enhancing tourist interest and influencing their visit decisions using the EPIC Model approach. Method: The research applies a mixed-method design that combines qualitative and quantitative approaches. The e-booklet was developed using the design thinking framework. Qualitative data were collected through in-depth interviews with tour organizers and local guides to gather content input for the e-booklet, while quantitative data came from questionnaires distributed to potential tourists. The questionnaire used a Likert scale to measure each dimension of the EPIC Model: Empathy, Persuasion, Impact, and Communication. Result: The e-booklet created through the design thinking process provides complete and detailed information about tourist activities, locations, travel tips, and booking contacts. This design makes information distribution easier, faster, and better suited to the preferences of today’s digital travelers. Based on the EPIC Model assessment, the e-booklet proved to be highly effective as a digital promotional tool that strengthens emotional connection, builds a positive image, and increases tourist interest in visiting marine ecotourism destinations in Karimunjawa. Contribution: The study contributes to the development of digital promotion strategies for marine ecotourism that align with current tourism trends, especially in Karimunjawa. In addition, the e-booklet is expected to help attract more visitors to join the Jokka Jokka Kemujan Tour, and supporting tourist participation and the growth of the local tourism sector.